EARLY WARNING TERHADAP INSIDEN KEBAKARAN PADA OVER LAND BELT CONVEYOR PABRIK SEMEN MENGGUNAKAN LINEAR HEAT DETECTION SYSTEM - Ratna Ikawati; Widy Wibisono; Mulia F. Nasution; Ade Y Prasetya (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
The cement market is increasingly competitive with the rise of imported cement, which of course must be answered by cement producers among competition. One of the main processes that should not be disturbed is the supply of limestone from quarry to the factory. The safety of people, processes and equipment are certainly necessity for the production process to run smoothly. The problem that can occur in limestone supply is a breakdown on the Overland Belt Conveyor (OLBC) which is caused by a broken roller and causes the belt to tear and potentially fire. For this reason, prevention efforts need to be done with an early warning mechanism to provide alerts to interested parties. Early warning system can be applied to the process because it can detect the beginning of heat so that fires can be prevented. Therefore, it is necessary to install a sensor using optical fiber called a linear heat detector (LHD) on OLBC. Installing the LHD system on OLBC can effectively detect an increase in roller temperature which then becomes an early warning for operators in the control room 24 hours a day to prevent incidents that cause harm to the company due to belt fires or torn belts.